Proceedings of the 21st ACM Conference on Hypertext and Hypermedia 2010
DOI: 10.1145/1810617.1810647
|View full text |Cite
|
Sign up to set email alerts
|

Conversational tagging in twitter

Abstract: Users on Twitter, a microblogging service, started the phenomenon of adding tags to their messages sometime around February 2008. These tags are distinct from those in other Web 2.0 systems because users are less likely to index messages for later retrieval. We compare tagging patterns in Twitter with those in Delicious to show that tagging behavior in Twitter is different because of its conversational, rather than organizational nature. We use a mixed method of statistical analysis and an interpretive approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
153
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(156 citation statements)
references
References 13 publications
(10 reference statements)
2
153
0
1
Order By: Relevance
“…Huang et al further characterize the temporal dynamics of hashtags via statistical measures such as standard deviation and discover that some hashtags are used widely for a few days but then disappear quickly [9]. Recent research on collaborative filtering showed that the consideration of such temporal dynamics impacts recommendation quality significantly [10].…”
Section: Related Workmentioning
confidence: 99%
“…Huang et al further characterize the temporal dynamics of hashtags via statistical measures such as standard deviation and discover that some hashtags are used widely for a few days but then disappear quickly [9]. Recent research on collaborative filtering showed that the consideration of such temporal dynamics impacts recommendation quality significantly [10].…”
Section: Related Workmentioning
confidence: 99%
“…Various models have been proposed for studying and predicting general information diffusion on Twitter based on a combination of message content, user profiles and tweeting timings [6], [7], [8]. Romero et al [9] and Huang et al [10] studied the diffusion of #hashtags on Twitter and investigated the factors behind the mass adoption of #hashtags and their subsequent dying off.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Some use them as mass broadcast media for disasters or special events like elections. Hashtags are also used for brand promotion or micro-meme discussions [12]. Since hashtags are neither registered nor controlled by any user or group, it may be hard for some users to find appropriate hashtags for their tweets.…”
Section: Hashtag Recommendationmentioning
confidence: 99%